Media Edukasi dan Informasi dalam Podcast Lingkar Inspirasi Bangsa “Yuk Kita Bahas” - Pratama, Muhammad Habibi Putra; Harahap, Nursapia (Jurnal Pustaka Komunikasi, 2024)
The aim of this research is to find out whether the Lingkar Inspirasi Bangsa podcast can be a medium of education and information for the community, especially teenagers. The research method used is descriptive study research which focuses on searching for information related to existing symptoms, supported by an explanation of the objectives achieved. The data collection technique applied uses interviews and observation as primary data plus documentation as secondary data. The research results obtained are that every podcast episode that has been selected and watched by the informant, namely Duta Siswa Sumatera Utara 2022, becomes a new experience and learning so that any information and education obtained can be applied according to their individual needs.